Overlapping roles for the histone acetyltransferase activities of SAGA and Elongator in vivo - Wittschieben, Birgitte Ø. (Oxford University Press, 2000)
Elp3 and Gcn5 are histone acetyltransferases (HATs) that function in transcription as subunits of Elongator and SAGA/ADA, respectively. Here we show that mutations that impair the in vitro HAT activity of Elp3 confer typical elp phenotypes such as temperature sensitivity. Combining an elp3Δ mutation with histone H3 or H4 tail mutations confers lethality or sickness, supporting a role for Elongator in chromatin remodelling in vivo. gcn5Δelp3Δ double mutants display a number of severe phenotypes, and similar phenotypes result from combining the elp mutation with mutation in a gene encoding a SAGA-specific, but not an ADA-specific subunit, indicating that Elongator functionally overlaps with SAGA. Because concomitant active site alterations in Elp3 and Gcn5 are sufficient to confer severe phenotypes, the redundancy must be specifically related to the HAT activity of these complexes. In support of this conclusion, gcn5Δelp3Δ phenotypes are suppressed by concomitant mutation of the HDA1 and HOS2 histone deacetylases. Our results demonstrate functional redundancy among transcription-associated HAT and deacetylase activities, and indicate the importance of a fine-tuned acetylation–deacetylation balance during transcription in vivo.